Combining Cylindrical Bone Graft and Headless Screw Fixation for Nonunion of the Medial Trochlea of the Elbow: A Case Report. Issue 2 (18th April 2022) - Uno, Tomohiro; Honma, Ryusuke; Takahara, Masatoshi; Satake, Hiroshi; Oishi, Ryuta; Maruyama, Masahiro; Takagi, Michiaki
Abstract : Case: A 19-year-old handballer presented with elbow pain and nonunion of the medial trochlea of the elbow. He had undergone earlier surgery for an elbow injury at 6 years of age. Revision surgery for nonunion was performed using an extra-articular method combining cylindrical bone graft and headless screw fixation. Partial union was observed, and he resumed sports after 3 months, with his limb largely pain-free and functional. At the 21-month follow-up, bone healing was complete. Conclusions: Combining cylindrical bone graft and headless screw fixation using the extra-articular technique is an option for managing nonunion of the medial trochlea of the elbow.